Electric energy quality compensation monitoring system - WANG WEI; TANG QIAN; LI JING; ZHANG YI; BIAN XIN; ZHANG LIZHU (2018)
The invention discloses an electric energy quality compensation monitoring system which comprises a microprocessor, a communication module, a control terminal, an electromagnetic relay, an electric energy quality compensator, an electric energy data collection module, a storage module and a logic module, wherein the microprocessor is connected with the communication module, the communication module is connected with the control terminal, the microprocessor is connected with the electromagnetic relay, the electromagnetic relay is connected with the electric energy quality compensator, and the microprocessor is connected with the electric energy data collection module, the storage module and the logic module. Thus, abnormal electric energy quality can be found by monitoring, the power compensator can provide electric energy compensation, and thus, loss caused by abnormal electric energy quality can be reduced. 本发明公开了种电能质量补偿监测系统，包括微处理器、通信模块、控制终端、电磁继电器、电能质量补偿器、电能数据采集模块、存储模块和逻辑模块，所述微处理器连接通信模块，通信模块连接控制终端；所述微处理器连接电磁